Implementation of Hiwalah at Al-Ikhlas Batusangkar Public Employee Cooperative - Megi Saputra; Zainuddin Zainuddin (Saqifah: Jurnal Hukum Ekonomi Syariah, 2024)
The trigger for the problem in this study is the implementation of hiwalah contemporary on KPN Al-Ikhlas Batusangkar. This study describes the implementation of hiwalah contemporary at KPN Al-Ikhlas Batusangkar, as seen in classical economics and the fiqh contemporary economy. The research used is field research with a qualitative approach. Data was collected through interviews. Data analysis using Miles and Huberman analysis includes data collection, reduction, presentation, and conclusion. The results of the research show that the forms of debt diversion to KPN Al-Ikhlas Batusangkar include, hiwalah in murabahah al inah, and hiwalah in murabaha, and followed by ijarah lumpuriyah tamblik bit (IMBT). Causal factors for the transfer of debt to KPN Al-Ikhlas Batusangkar include not wanting to be involved in usury anymore, their returns in the form of distribution of remaining operating results (SHU), and no gifts to cooperatives to get financing. After being discussed, there was a modification of the hiwalah form by using multiple contracts and allowed to find economic profit in doing hiwalahor transfer of debt.